The Influence of Student Purchase Level on Increase in Micro, Small, and Medium Enterprises - Anggun Dwi Yulianah; Dimas Putra Pratama; Arjuna Kusuma Prayoga; Nihlatul Philasifah (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze the influence of student purchasing power on increasing the income of Micro, Small, and Medium Enterprises (MSMEs) in the UIN Sunan Ampel Surabaya environment. The presence of students as the main consumers in the campus area provides economic opportunities for MSMEs, especially canteen businesses and small businesses around the university. This study uses a quantitative approach, employing a survey method via the distribution of questionnaires to 32 respondents. The independent variable in this study is the level of student purchasing power, while the dependent variable is the increase in MSME income. Data were analyzed using validity, reliability, and normality tests; linear regression; t-tests; F-tests; and coefficients of determination in SPSS. The results show that student purchasing power has a positive, significant effect on MSME income. The regression coefficient of 0.537 indicates that higher student purchasing power is associated with higher MSME income. The results of the t-test show a significance value of 0.006 < 0.05, and the F-test also shows a significant effect. The coefficient of determination indicates that student purchasing power partially explains the variation in MSME revenue growth. At the same time, other factors, such as price, product quality, location, service, menu variety, cleanliness, comfort, and promotional strategies, account for the remaining variation. This study emphasizes the importance of MSMEs understanding student consumption behavior to optimize and sustainably increase business revenue.